HYBRIDIZATION of GOLD FISH (Carassius auratus auratus) with TAWES (Barbonymus gonionutus) - Zulfirman Ginting; Nuraini '; Sukendi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted from April-December 2014 in Hatchery andBreeding Laboratory, Faculty of Fisheries and Marine Sciences, University ofRiau. The objective of this research was to evaluate the intergeneric hybridizationbetween gold fish (Carassius auratus auratus) with silver barb fish (Barbonymusgonionotus) by comparing the fertilization rate, hatching rate, survival rate in fourdays (SR-4), survival rate for 30 days (SR-30), extra weight and value heterosis (hybrid vigor ) between fish larvae results hybridization with fish control. Themethod is applicable in the experimental methods, where spawning artificial wasconducted by the use of eggs and fish sperm of a comet (Carassius auratusauratus) and silver barb (Barbonymus gonionotus) that has been injected usingovaprim with a dose of 0,5ml / kg.The highest percentage of fertilization is marriage ♂ K x ♀ K (88,8%),follow by ♀ K x ♂ T (85,505%), ♀ T x ♂ T (36,65%) ♀ T x ♂ K 0%. The highestpersenatage hatching is a control that is ♂ T x ♀ K (94.285%), which followed ♀K x ♂ K (74,655%), ♀ T x ♂ T (54,72%) and ♀ T x ♂ K (0%). The highestpercentage of survival rate 30 days in sequence is ♀ K x ♂ T (44,97%), ♀ K x ♂K (41,985%) and ♀ T x ♂ T (6,15%). The highest weight added sequentially isthe larvae of spawning results ♀ K x ♂ K (0,513 g), ♀ T x ♂ T (0,343 g) dan ♀ Tx ♂ K (0,328 g). All values of heterosis is negative except at the heterosis B butnot the absolute weight.Key words : hibrydization, gold fish, silver bard